Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/jbg.12022
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of dominance and inbreeding depression in estimating variance components for litter size in Pannon White rabbits

Abstract: In a synthetic closed population of Pannon White rabbits, additive (VA ), dominance (VD ) and permanent environmental (VPe ) variance components as well as doe (bF d ) and litter (bF l ) inbreeding depression were estimated for the number of kits born alive (NBA), number of kits born dead (NBD) and total number of kits born (TNB). The data set consisted of 18,398 kindling records of 3883 does collected from 1992 to 2009. Six models were used to estimate dominance and inbreeding effects. The most complete model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
6
18
4
Order By: Relevance
“…Pearson's correlations showed the same tendencies as observed for the rank correlations but slightly higher values were found (Table 4). In the Pannon White rabbit population Nagy et al (2013) reported Spearman's rank correlations between breeding values estimated with the different single-trait models close to unity for NBA, NBD, and TNB. Similarly, Gallardo et al (2010) observed that the estimated breeding values of harvest body weight in Coho salmon showed correlation close to unity when the applied single-trait models differed only in the inclusion of the dominance effects.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Pearson's correlations showed the same tendencies as observed for the rank correlations but slightly higher values were found (Table 4). In the Pannon White rabbit population Nagy et al (2013) reported Spearman's rank correlations between breeding values estimated with the different single-trait models close to unity for NBA, NBD, and TNB. Similarly, Gallardo et al (2010) observed that the estimated breeding values of harvest body weight in Coho salmon showed correlation close to unity when the applied single-trait models differed only in the inclusion of the dominance effects.…”
Section: Resultsmentioning
confidence: 94%
“…However, Nagy et al (2011) evaluated the records of the first four parities only over a shorter period thus the size of the evaluated dataset was substantially smaller (3413 kindling records) than in the present study. In the Pannon White rabbit population Nagy et al (2013) used numerous models. When the models contained the same effects as the basic model of this study, slightly lower h 2 and p 2 estimates were obtained for NBA (0.057 and 0.066), NBD (0.022 and 0.015), and TNB (0.064 and 0.069) compared to the findings of this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incomplete and unbalanced pedigree information is one source of errors (Cassell et al, 2003) in estimation of inbreeding depression. In experimental analyses, different strategies have been applied to account for the bias introduced by incomplete pedigrees (VanRaden, 1992;Lutaaya et al, 1999;González-Recio et al, 2007 andNagy et al, 2013). Pedigree errors are another source of errors that is present in livestock populations (Leroy and Baumung, 2011).…”
Section: Classical Approach Of the Inbreeding Depression Estimationmentioning
confidence: 99%